The Influence Facility Work on The Employee's Performance of Vocational High School of Rosma Karawang District - Indriyanti, Veronica Pangesti; Solehudin, Solehudin (Universitas Mercu Buana, 2024)
The potential of every human resource in an organization must be utilized as well as possible so as to be able to provide optimal work results. The achievement of the goals set by an organization does not only depend on modern equipment, complete facilities and infrastructure, but also depends on the people who carry out the work. The success of an organization is greatly influenced by the performance of individual employees. This study aims to determine the effect of staff organization on staff performance in Rosma Vocational Secondary School, Karawang District. This type of research is quantitative research using descriptive and observational research methods. There are 69 samples in this study. The survey method used in this study is a satisfaction survey. The research findings of this study use a multi-line exploratory research method. The results showed that Rosma Vocational High School, Karawang District, is among the institutions that affect employee performance